2007
DOI: 10.2353/jmoldx.2007.060088
|View full text |Cite
|
Sign up to set email alerts
|

Telomeric IGH Losses Detectable by Fluorescence in Situ Hybridization in Chronic Lymphocytic Leukemia Reflect Somatic VH Recombination Events

Abstract: Chromosomal translocations affecting the immunoglobulin loci, particularly immunoglobulin heavy chain (IGH) genes complex at 14q32, are a hallmark of B cell malignancies.1,2 They usually result in deregulated expression of involved oncogenes (eg, BCL1, CMYC, and PAX5) juxtaposed to the regulatory elements of IGH. As some of these translocations are associated with specific subtypes of mature B cell lymphoma and have prognostic significance, their detection is of clinical importance. In daily practice, IGH tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 22 publications
3
29
1
Order By: Relevance
“…A gain of IGH signals could possibly signify trisomy 14, which is considered as a rare event in MM [Kumar et al, 2012]. However, nonspecific patterns not related to IGH rearrangements due to cohybridization of IGH green signals in 15q11 and 16p11.2 are also well described [Wlodarska et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A gain of IGH signals could possibly signify trisomy 14, which is considered as a rare event in MM [Kumar et al, 2012]. However, nonspecific patterns not related to IGH rearrangements due to cohybridization of IGH green signals in 15q11 and 16p11.2 are also well described [Wlodarska et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…No falsenegative signal for t(4; 14) was identified, even if associations between IGH deletions and IGH translocations are well described in studies and were found in 22.7% of newly diagnosed MM [He et al, 2015]. IGH loss or partial deletion may be part of a physiological event or part of an oncogenic process of B-lineage cells [Fink et al, 2005;Pospisilova et al, 2007;Wlodarska et al, 2007]. When they are part of an oncogenic process, they may be considered as additional chromosomal aberrations and associated with a decrease of overall survival [Leiba et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…37 ). On the other hand, the detected deletions tend to associate with additional chromosomal changes, such as trisomy 12 and IgVH unmutated status 38 . Both cases with 3´IgH deletion were unmutated, as well as 7 out of 10 cases with 5´IgVH deletion, and in all cases additional changes were observed.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of one fusion signal and one single-color signal (either red or green) was considered as indicative of deletion of part of the Ig gene, a phenomenon reflecting physiologic rearrangement of the IgH gene. 26 Cut-off for positivity. To establish the cutoff, we used 10 cases of reactive tonsil, spleen and thymus tissues arranged in the five TMAs plus two reactive lymph nodes on two separate slides.…”
Section: Immunohistochemistrymentioning
confidence: 99%